Pengaruh Brand Awareness, Daya Tarik Iklan,Perceived Quality,Dan Knowledge Halal Product Terhadap Keputusan Pembelian Geprek Kak Rose Di Kota Malang - Egy Hana Maghfira; Mohammad Rizal; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of brand awareness, advertising attractiveness, perceived quality, and knowledge of halal products on purchasing decisions of Geprek Kak Rose (a case study on Geprek Kak Rose consumers). This study used a quantitative research type. The sampling technique used the Malhotra formula and the results obtained were 85 respondents. The data collection was carried out using a questionnaire. Data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis Test (f test), and t test). Coefficient of Determination (Adjusted R2) and Process analysis using SPSS 21. The results of the study stated that the variable brand awareness and perceived quality had a significant effect on purchasing decisions while the attractiveness of advertisements and knowledge of halal products had no significant effect on purchasing decisions.  Keywords: Brand Awareness,Advertising Attractiveness,Perceived Quality Knowledge Halal Products